2020
DOI: 10.1001/jamanetworkopen.2020.0701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Person Assistance vs Personalized Written Resources About Social Services on Household Social Risks and Child and Caregiver Health

Abstract: IMPORTANCE Social and economic contexts shape children's short-and long-term health. Efforts to address contextual risk factors are increasingly incorporated into pediatric health care. OBJECTIVE To compare the effectiveness of 2 social risk-related interventions. DESIGN, SETTING, AND PARTICIPANTS This randomized clinical trial included English-and/or Spanish-speaking caregiver-child dyads recruited from a pediatric urgent care clinic nested in a large,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
136
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 70 publications
(139 citation statements)
references
References 64 publications
1
136
0
2
Order By: Relevance
“…One study found that compared with patients who receive only written materials on community services, patients who receive on-site patient navigation services report reductions in unmet social needs and improvements in parent-reported child health outcomes, 10 while another similar study found no difference between the 2 groups. 11 As patient navigation interventions have expanded into pediatric health care delivery systems, issues have arisen regarding implementation barriers and utilization of these interventions. 12 Unfortunately, while in-person patient navigation is preferred by patients and physicians, it is often not feasible due to lack of financial resources and space.…”
mentioning
confidence: 99%
“…One study found that compared with patients who receive only written materials on community services, patients who receive on-site patient navigation services report reductions in unmet social needs and improvements in parent-reported child health outcomes, 10 while another similar study found no difference between the 2 groups. 11 As patient navigation interventions have expanded into pediatric health care delivery systems, issues have arisen regarding implementation barriers and utilization of these interventions. 12 Unfortunately, while in-person patient navigation is preferred by patients and physicians, it is often not feasible due to lack of financial resources and space.…”
mentioning
confidence: 99%
“…The authors conducted a randomized clinical trial (RCT) in a pediatric urgent care clinic at an urban safety-net hospital to compare the efficacy of 2 interventions on reducing social risks and improving child and caregiver health 6 months after enrollment. 1 Caregiver-child dyads were screened for 18 social risk factors (eg, housing stability, food, employment) and randomized to receive either written information about available social services or written information plus in-person social services navigation assistance for their identified risks. Navigators assisted with scheduling appointments and completing forms and were in contact with caregivers via telephone, text message, or email every 2 weeks for up to 3 months.…”
mentioning
confidence: 99%
“…The WE CARE screening consisted primarily of a self-reported 6-item social risk screener that triggered parental receipt of written resource sheets and social service applications only when parents indicated wanting help. The findings of the study by Gottlieb et al, 1 along with results from the 2015 trial, 3 suggest that pediatric practices, regardless of size and support staff, can address patients' unmet social needs by handing out high-quality written information. As Gottlieb housing voucher recipients compared the receipt of housing voucher information alone with housing voucher receipt and navigation assistance and found no difference in moving rates.…”
mentioning
confidence: 99%
See 2 more Smart Citations